Optimalisasi Pemanfaatan Lahan Pasang Surut Untuk Budidaya Cabai Rawit Bonita IPB di Desa Banyu Urip, Kecamatan Tanjung Lago, Banyuasin - Karlin Agustina Bastomi; Yursida; Pandriadi; Evriani Mareza; Tedy Martadela; Fifi Mutia (Altifani Journal: International Journal of Community Engagement, 2024)
Cayenne pepper is one type of chili that is widely consumed. The variety of Indonesian cuisine that uses cayenne pepper as a raw material has increased the need for cayenne pepper in Indonesian society. Efforts to increase cayenne pepper production include using superior varieties and through extensification by utilizing suboptimal land. One of the superior cayenne peppers resulting from research by the IBA University team together with the IPB chili consortium is the Bonita IPB cayenne pepper which has received legalization of variety release from the Indonesian Ministry of Agriculture with Decree number 343/Kpts/SR.130/D/IV/2021 concerning the Issuance of a Registration Mark for Horticultural Plant Varieties Bonita IPB Chili dated April 26, 2021. This cayenne pepper is suitable for development in tidal land. One of the tidal areas that has the potential for the development of Bonita IPB cayenne pepper is located in Banyu Urip Village, Tanjung Lago District. The author's team seeks to provide solutions to the problems of production and marketing of agricultural products by increasing knowledge and capacity as well as improving the community's economy, especially in the Tani Mukti Farmer Group which is the target partner. The implementation method of the activity includes: 1) survei, observation and identification of partner problems, 2) licensing, partner approaches and socialization, 3) training, guidance and assistance, 4) application of technology/creation of demo plots and 5) monitoring and evaluation. The results of the activity have been carried out by making a demo plot on low land owned by Mr. Ponio, a member of the Tani Mukti farmer group located in Banyu Urip Village RT.04 Dusun 1 Jembatan 4. Currently the plants are 3 months old and have started to bear fruit. The farmers have been given training on the cultivation of Bonita IPB cayenne pepper plants, chili plant pests and diseases and control techniques and digital marketing of agricultural products.